Maternal and neonatal outcome among referred women - Monika; Verma, Krupa; Panwar, Babita; Hooja, Nupur; Kaswan, Prem Preet; Yadav, Shivangi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: The availability of emergency obstetric care is considered to be an indicator of the preparedness of a health care services. Timely referral plays an important role in the management of diseases in any healthcare system. Methods: This study included all referred women admitted in the hospital with more than 20 weeks gestational age. 220 referred women were included in the study. All details were noted and women were monitored. Maternal and foetal outcome were analysed. Results: Caesarean section was performed in 58.32% of those delivered. 75.72% of neonates had 7 or higher APGAR score. There were 5.78% stillbirths. Conclusions: The study showed good referral practices from most referring centres. Overall maternal and neonatal outcome was good. Utilizing community health workers to educate and identify high risk women for frequent antenatal care and early referrals will improve maternal outcome.